Persepsi Tax Amnesty Sebagai Pemoderasi Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan Pada Kepatuhan WPOP - Sari, Andini Permata; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p18, 2018)
Tax is a taxpayer contribution payable by an individual or a coercive entity under statutory regulations, not obtaining direct contracting but used to finance the needs of the state which would later be expected to have an impact on the increase of income and the welfare of society. Some factors that can improve taxpayer compliance are taxpayer awareness, tax sanctions and tax amnesty policy. Tax amnesty policy is one of the government programs in the field of taxation to increase tax revenue and the number of taxpayer, where the policy is implemented by granting tax pardons to taxpayer who do not perform tax obligations. This study aims to empirically examine the influence of awareness of taxpayer and tax penalties on the personal taxpayer compliance with tax amnesty as a moderator. This search was conducted in Kantor Pelayanan Pajak Pratama Badung Utara. Samples taken as many as 100 personal taxprayers which is calculated based on the slovin formula, determined by accsidental sampling method. Data was collected using questionnaires. Analysis technique used is the Multiple Linear Regression Analysis and Moderate Regression Analysis (MRA). Based on the analysis concluded that awareness of taxpayers and tax penalties have a positive and significant effect on the personal taxpayers compliance. Tax amnesty perception can not moderate the influence of awareness of taxpayers on the personal taxpayers compliance, but tax amnesty perception can moderate the influence of tax penalties on the personal taxpayers compliance. Keywords: Tax Amnesty Perception, Awareness of Taxpayers, Tax Penalties, Personal Taxprayers Compliance